Pengaruh Non Performing Loan (NPL) Dan Biaya Operasional Dan Pendapatan Operasional (BOPO) Terhadap Harga Saham Pada PT. Bank Artha Graha Internasional, Tbk - Amalya, Nurita; Alwi; M. Rimawan (Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to determine the Effect of Non Performing Loans (NPL) and Operating Costs Operating Income (BOPO) on Stock Prices at PT. Bank Artha Graha Internasional, Tbk). This study uses an associative research type. The research instrument used in this study is a list of tables containing data on total non-performing loans, total credit, operating costs, operating income and stock prices at PT. Bank Artha Graha Internasional, Tbk for 10 years, namely from 2014 to 2023. The population in this study was 43 years. The sample in this study was the financial statements of PT. Bank Artha Graha Internasional, Tbk for 10 years, namely from 2014 to 2023 with a purposive sampling technique. Data collection techniques are documentation and literature studies. The analysis techniques used in this study are classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests. The results of the study indicate that Non Performing Loan (NPL) and Operating Costs and Operating Income (BOPO) have a significant effect partially and simultaneously on stock prices at PT. Bank Artha Graha Internasional, Tbk.